Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Cafe Resto Solid Kitchen Di Surakarta - Faizal Assidiq, Muhammad, Drs. Sujadi, MM (2016)
This research is written to know the quality service toward consumers' satisfaction at Solid Kitchen Café and Restaurant in Surakarta. Also to know the variables which affect the most toward the consumers' satisfaction in Solid Kitchen Café and Restaurant in Surakarta. The method of analysis is doubled linier regression, which takes the data by giving questionnaires to a hundred respondents in Solid Kitchen Café and Restaurant in Surakarta. This research refers to a positive approach; an approach which started by a hypotheses then continued by testing the hypotheses itself. Based on result of the doubled linier regression test, we can know that the fifth variables of quality service which are: responsiveness, assurance, tangibles, emphaty, and reliability, have significant effect toward the consumers' satisfaction. Variable of tangibles affect the most toward the variable of consumers' satisfaction. This can be seen from the result of the doubled linier regression test and partial significance test (the t-test), which is the smallest than the variables of responsive, assurance, emphaty, and reliability. This result is in compliance with the research done by Aryani and Rosinta (2010) which declares that the fifth dimensions which shape quality service (reliability, responsiveness, assurance, emphaty, and tangibility), proved affect significantly toward the consumers' satisfaction. The research done by Mugiono (2010) also declares that tangibles, reliability, responsiveness, assurance, and emphaty variables affect the degree of consumers' satisfaction, both in partially and simultaneously, proved by the accuracy toward a high linier model. Along with the research done by Kusuma and Budiadi (2013), declares that quality service which consists of tangibles, reliability, assurance, emphaty, and responsiveness, affect significantly partial and simultaneous, do together toward consumers' satisfaction. Result of the research shows that the fifth variables of quality service - responsiveness, assurance, tangibles, emphaty, and reliability affect significantly toward variable of consumers' satisfaction and have a positive effect toward consumers' loyalty, based on the mount of the total guests. This proved by the result which shows that 19.7 percent from variable of consumers' satisfaction can be described by variable of quality service, whereas the balance that is 80.3 percent described by another factors beyond variable of quality service. Thus, by this research, businessmen are expected better to pay attention at quality service, because with a good quality service, consumers will be attracted to buy products or commendable that offered. Key words: quality service, consumers' satisfaction.